Fiber-reinforcement MICP for Durability Improvements - Daryono, Lutfian Rusdi; Abe, Tomohiko; Kano, Masanao; Nakashima, Kazunori; Kawasaki, Satoru (Indonesian Geotechnical Journal, 2024)
Microbially Induced Carbonate Precipitation (MICP) technology, a method for soil enhancement, has recently garnered considerable attention within geotechnical communities. This study places a significant focus on addressing the paramount concern pertaining to the endurance of MICP-treated specimens. The research centers on MICP-treated samples fortified with plant-derived natural fibers, specifically jute. It evaluates their robustness when subjected to exposure to both distilled water (DW) and artificial seawater (ASW). The primary objectives encompass acquiring a comprehensive understanding of their prolonged performance under varied conditions, appraising the consequences of fiber reinforcement, and augmenting the suitability of MICP-treated samples for applications in the safeguarding of coastal regions against erosion. The investigation subjected these specimens to 12 wetting-drying cycles utilizing artificial seawater following treatment periods of 5 days, 7 days, and 14 days. The findings unveiled an approximate 8.5% diminution in sample mass, with the fibers constituting 2% of the sand's total weight. Moreover, the study underscores the adeptness of the integrated fiber in withstanding the wetting-drying (WD) cyclic process, amplifying the mechanical and physical attributes of the fiber-reinforced MICP-treated specimens, thus contributing significantly to their overall durability.